The Experiences of Patients with Diabetes and Strategies for Their Management during the COVID-19 Pandemic: a Qualitative Study - Anita Joeliantina; Irfany Nurul Hamid; Endang Sulistyowati (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
The COVID-19 pandemic has posed significant challenges for individuals with chronic conditions like Diabetes Mellitus (DM), especially in terms of maintaining proper self-care. This qualitative study aimed to explore the self-care experiences of patients with DM during the pandemic, with a focus on the impact of restricted access to healthcare services and changes in daily routines. The study adopted a phenomenological approach, involving ten purposively selected DM patients from the Keputih Health Center in Surabaya, Indonesia. Data were collected through semi-structured in-depth interviews, both online and offline, between August and October 2021. The Van Manen method was utilized for data analysis. The results revealed five key themes: poor diabetic diet, absence of physical activity, impaired monitoring of blood glucose levels, changes in medication patterns, and neglect of foot care. These findings indicate a significant decline in self-care behaviors, largely attributed to restricted movement, limited access to health services, and heightened fear of COVID-19 transmission. The study also highlighted the use of herbal remedies as a supplementary treatment, a behavior not widely reported in previous research. The study concludes that diabetes management during the pandemic was adversely affected, emphasizing the need for tailored interventions, including online consultations and education, to support DM patients. Further research is recommended to explore effective strategies for managing DM during health crises, particularly the integration of traditional and medical treatments.